Using Eye-Tracking Technology for the Analysis of Students’ Subjective Views on Usefulness of Chosen Physics Formulas - PĘCZKOWSKI, PAWEŁ; BŁASIAK, WŁADYSŁAW (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
This paper is the second part of research concerning students’ view on usefulness of physics formulas. In the first part we examined subjective students’ opinions on the usefulness of selected physics formulas from the school curriculum. No we concentrated on eye-tracking experiments. Students have assessed 16 of the most important physics formulas, chosen by physics teachers. For deeper understanding of student’s choices on eye-tracking has been conducted. For 52 students divided on two groups: not participating in school competitions in physics and other natural sciences named “ordinary students” and participating in these competitions named “extraordinary students”, a relationship was observed between their eyes’ fixation time (divided into Area of Interest) on 16 displayed formulas and the frequency of recognizing these as useful. We compared also saccade duration time between these two groups of students. Physics contest winners found over 60% of these formulas useful, whereas the average students’ result was less than 30%. We observed a positive correlation between the number of eye-fixations on a given formula and the frequency of selection by the students as useful. Students that showed more interest in the selected subjects also perceived the areas of study presented by them to be much more useful to the society. It has also been concluded that the intention of choosing one’s profession within the area of a given subject depends on one’s interest in the subject.